1995
DOI: 10.1182/blood.v86.9.3535.bloodjournal8693535
|View full text |Cite
|
Sign up to set email alerts
|

Effect of all-trans retinoic acid on procoagulant and fibrinolytic activities of cultured blast cells from patients with acute promyelocytic leukemia

Abstract: The mechanisms underlying acute promyelocytic leukemia (APL) coagulopathy and its reversal by administration of all-trans retinoic acid (ATRA) have been investigated. Bone marrow promyelocytic blasts from nine patients with APL were cultured with or without ATRA 1 mumol/L. Cultured blasts (days 0, 3, 6, and 9) were washed, resuspended in phosphate buffer, lysed by freezing and thawing, and then assayed for procoagulant activity (PCA), elastase activity, tissue factor (TF) antigen, tissue-type plasminogen activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 17 publications
2
32
0
2
Order By: Relevance
“…However, a later study demonstrated lower levels of fibrinolytic and proteolytic activity in APL blasts compared with mature neutrophils. In this study, use of ATRA was not associated with changes in protease activity of APL cells [24]. In another study, no correlation was noted between elastase levels and D‐dimer concentration or other hemostatic parameters during treatment with ATRA.…”
Section: Proteolysismentioning
confidence: 65%
See 1 more Smart Citation
“…However, a later study demonstrated lower levels of fibrinolytic and proteolytic activity in APL blasts compared with mature neutrophils. In this study, use of ATRA was not associated with changes in protease activity of APL cells [24]. In another study, no correlation was noted between elastase levels and D‐dimer concentration or other hemostatic parameters during treatment with ATRA.…”
Section: Proteolysismentioning
confidence: 65%
“…Both CP and TF have been identified in the human APL cell line NB4 [19, 21]. In vitro studies have demonstrated that ATRA‐induced APL cell differentiation causes loss of expression of CP [22] and TF [23, 24]. TF and CP expression is decreased in bone marrow cells of APL patients given ATRA for remission induction and this decrease precedes normalization of lab abnormalities of coagulation [25].…”
Section: Procoagulant Activity (Pca)mentioning
confidence: 99%
“…Thus, cancer cells may produce high levels of blood coagulation factors, including factor V (FV), FVIII, FIX and FXI, 15 while many cancer cell types (e.g., leukaemia and colon cancer) express tissue factor. [30][31][32] These alternations then lead to enhanced coagulant activities and thrombin generation. Indeed, cancer patients are often seen with signs of hypercoagulant activities, such as elevated plasma levels of D-dimers, thrombin-antithrombin complex and prothrombin fragment 1 1 2.…”
Section: A Brief Review Of Thrombosis-cancer Associationmentioning
confidence: 99%
“…15,42 Malignancy may also induce the disturbance of fibrinolysis system, either with hyperfibrinolytic or hypofibrinolytic alterations. 15,31 The disturbances of coagulation system may then lead to exaggerated platelet activation.…”
Section: A Brief Review Of Thrombosis-cancer Associationmentioning
confidence: 99%
“…Several authors have identified TF in these cells. 47,[67][68][69] Falanga et al [57][58][59] reported the identification of CP in acute myelogenous leukemia blast cells of various phenotypes, with the greatest expression in cultured cells from patients with the acute promyelocytic leukemia (APL) subtype. Recent data showed that all-trans-retinoic acid (ATRA) can influence the expression of PCA in cultured APL cells in vitro.…”
Section: Procoagulant Activitymentioning
confidence: 99%